2023
DOI: 10.1088/2058-9565/acc968
|View full text |Cite
|
Sign up to set email alerts
|

Is everything quantum ‘spooky and weird’? An exploration of popular communication about quantum science and technology in TEDx talks

Abstract: Previous studies have identified four potential issues related to the popularisation of quantum science and technology. These include framing quantum science and technology as spooky and enigmatic, a lack of explaining underlying quantum concepts of quantum 2.0 technology, framing quantum technology narrowly in terms of public good and having a strong focus on quantum computing. Before assessing the effect of these potential issues on public perceptions, it is important to first determine whether these issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A study specifically on the framing of quantum physics and technology by experts and non-experts in TEDx talks found that while quantum science is explained in half of the talks, it is often framed narrow, focussing on the benefits rather than risks. Furthermore, about a quarter of the talks frame quantum science and technology as spooky (Meinsma et al 2023). It is yet unknown what the effect of such framing is on the public perception of quantum, but it is expected to create a distance between technology and the public Grunwald 2017, Vermaas 2017).…”
Section: Public Perception Of New Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study specifically on the framing of quantum physics and technology by experts and non-experts in TEDx talks found that while quantum science is explained in half of the talks, it is often framed narrow, focussing on the benefits rather than risks. Furthermore, about a quarter of the talks frame quantum science and technology as spooky (Meinsma et al 2023). It is yet unknown what the effect of such framing is on the public perception of quantum, but it is expected to create a distance between technology and the public Grunwald 2017, Vermaas 2017).…”
Section: Public Perception Of New Technologiesmentioning
confidence: 99%
“…Vermaas (2017) states that discussions about quantum technology will be useful only when all parties involved have at least a fundamental understanding of quantum science. A barrier to this process could be the current framing of quantum science as enigmatic and counterintuitive rather than as a novel but understandable part of physics (Meinsma et al 2023).…”
Section: Societal Readiness Of Quantum Technologymentioning
confidence: 99%
“…A study specifically on the framing of quantum physics and technology by experts and non-experts in TEDx talks found that while quantum science is explained in half of the talks, it is often framed narrow, focussing on the benefits rather than risks. Furthermore, about a quarter of the talks frame quantum science and technology as spooky (Meinsma, Kristensen, Reijnierse, Smeets, & Cramer, 2023). It is yet unknown what the effect of such framing is on the public perception of quantum, but it is expected to create a distance between technology and the public (Coenen & Grunwald, 2017;Vermaas, 2017).…”
Section: Public Perception Of New Technologiesmentioning
confidence: 99%